(untitled) (International Current Pharmaceutical Journal, 2012)
In this study, a solubility enhancing technique, Self-emulsifying drug delivery system (SEDDS), was considered to be developed for Ibuprofen, a poorly soluble drug. Capmul PG 8 was used as a co-solvent. As surfactant, hydrophilic surfactant Cremophor EL was considered. A fixed amount of Ibuprofen was added with fixed amount of excipients. Capmul PG8 showed a good solubilizing capacity which dissolved 300 mg/ml of Ibuprofen. Cremophor EL also showed a good solubilizing capacity which dissolved 300 mg/ml of Ibuprofen. Ibuprofen is a poorly soluble drug which was used as experimental drug and pH 7.2 phosphate buffer was used as dissolution medium. The amount of drug was measured form the absorbance of UV spectrophotometer at 221 nm. A 3-level factorial design was carried out to optimize the formulation using design expert software trial version 8.0.3.1. Capmul PG8 and Cremophor EL were used as independent variables where percent drug release at 5, 15 and 45 minutes. The optimized formula contains 24.10 mg Capmul PG8 and 71.02 mg Cremophor EL which releases 27.78%, 44.6% and 74.24% ibuprofen at the mentioned time interval. The present study shows that the Capmul PG8 and Cremophor EL have effect the release profile of capsule Ibuprofen. It is found that it is possible to increase the release of Ibuprofen by using Capmul PG8 and Cremophor EL. DOI: http://dx.doi.org/10.3329/icpj.v1i6.10535 International Current Pharmaceutical Journal 2012, 1(6): 138-150